2017
DOI: 10.1002/num.22161
|View full text |Cite
|
Sign up to set email alerts
|

A modified method of approximate particular solutions for solving linear and nonlinear PDEs

Abstract: The method of approximate particular solutions (MAPS) was first proposed by Chen et al. in Chen, Fan, and Wen, Numer Methods Partial Differential Equations, 28 (2012), 506–522. using multiquadric (MQ) and inverse multiquadric radial basis functions (RBFs). Since then, the closed form particular solutions for many commonly used RBFs and differential operators have been derived. As a result, MAPS was extended to Matérn and Gaussian RBFs. Polyharmonic splines (PS) has rarely been used in MAPS due to its condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, it can often greatly affect the generalization capability of the RBF. Cao et al [30] discussed how high-order polynomial-augmented RBFs outperformed standalone RBFs and reduced the dependency of the RBF on the shape factor ϵ, and several works [31,32] have shown that adding high-order polynomials to the RBF greatly enhances the accuracy of the model. In this work, the polynomial-augmented RBF takes the form:…”
Section: Appendix a K-nearest Neighbor Polynomial-augmented Radial Ba...mentioning
confidence: 99%
“…However, it can often greatly affect the generalization capability of the RBF. Cao et al [30] discussed how high-order polynomial-augmented RBFs outperformed standalone RBFs and reduced the dependency of the RBF on the shape factor ϵ, and several works [31,32] have shown that adding high-order polynomials to the RBF greatly enhances the accuracy of the model. In this work, the polynomial-augmented RBF takes the form:…”
Section: Appendix a K-nearest Neighbor Polynomial-augmented Radial Ba...mentioning
confidence: 99%
“…Recently, the MAPS has been used to solve three-dimensional linear and nonlinear PDE. MAPS using polyharmonic splines and an additional polynomial of degree 15 is used in Yao et al (2017) to obtain results comparable to those obtained using multiquadric (MQ) RBFs. In Lamichhane et al (2016), a fast summation method, based on the Chebyshev interpolation, is employed with the MAPS to reduce computational effort when using Gaussian RBFs as source term in the auxiliary Poisson equation.…”
Section: Introductionmentioning
confidence: 99%